Gas Management in Coal-Gas Outburst Mines: Deep Analysis of Present Status and Future Tech Outlook - Zhang, Yong (Scientific Journal of Technology, 2026)
Pingdingshan Tian’an Coal Industry Co., Ltd. No.13 Mine is a typical coal and gas outburst mine, and gas disaster control is crucial to its safe and efficient production as well as sustainable development. Based on the mine’s mining intensity assessment and production capacity confirmation report, this paper systematically and in-depth analyzes the characteristics of gas occurrence, gas control technology system, configuration of gas extraction system and current status of management and operation in the mine. The research shows that Pingmei No.13 Mine has established a three-dimensional comprehensive gas control model with "low drainage roadway cross-layer drilling pre-extraction" as the core and "soft rock protective layer mining + pressure relief extraction" as the auxiliary. The capacity of the gas extraction system fully meets the current production needs, the control effect is remarkable, and the residual gas content in the coal seam has been effectively controlled. On this basis, combined with the practical challenges faced by deep mining, this paper looks forward to the development direction of gas control technology in the future from four dimensions: precise extraction, intelligent monitoring, green emission reduction and multi-disaster coordinated control, aiming to provide practical reference and technical guidance for gas control in similar coal and gas outburst mines in China.